1989
DOI: 10.1002/bms.1200180708
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of matrices used for fast atom bombardment

Abstract: Physical and chemical properties of common matrices are tabulated, with aims of facilitating rational matrix selection and providing input for fundamental studies of matrix-assisted ionization. The rationale for selecting tabulated properties is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…As a consequence, the average lifespan of the ES droplet increases, which in turn causes less evaporative cooling . Thus, m ‐NBA acts as both droplet temperature enhancer and chemical denaturant inside the ES droplet (dielectric constant of m ‐NBA is lower than that of water; see Table ) to unfold or partially unfold the protein, that in turn enhances the charging of the protein . This mechanism is still under controversy because this could not interpret the supercharging of the small analytes such as small organic molecule or peptide, which do not posses any tertiary structure .…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the average lifespan of the ES droplet increases, which in turn causes less evaporative cooling . Thus, m ‐NBA acts as both droplet temperature enhancer and chemical denaturant inside the ES droplet (dielectric constant of m ‐NBA is lower than that of water; see Table ) to unfold or partially unfold the protein, that in turn enhances the charging of the protein . This mechanism is still under controversy because this could not interpret the supercharging of the small analytes such as small organic molecule or peptide, which do not posses any tertiary structure .…”
Section: Resultsmentioning
confidence: 99%
“…However, in conjunction with compilations of matrix physical properties (e.g., ref. 46), consideration of data like those in Table 1 should facilitate efforts to rationalize matrix optimization.…”
Section: Discussionmentioning
confidence: 99%
“…In this study several commonly used matrices were tested,8 but it was found that the most abundant molecular ion species [M 2+ − H + ] + and [M 2+ + e − ] +· of porphyrin salts were observed either with SGLY or with NBA. The known electron‐ and especially radical‐acceptor properties of NBA9 were found to be important.…”
Section: Methodsmentioning
confidence: 99%